Ion channels - Fermini, Bernard. (Springer, 2017)
Ion channels play a vital role in basic physiological functions such as generation of electrical activity in nerves and muscle, control of cardiac excitability, intracellular signaling, hormone secretion, cell proliferation and many other biological processes. Because of their prevalence and the critical role they play in virtually all tissue types and organs, ion channels are also involved in a number of pathophysiological conditions. The aim of this volume is to review recent advances in the field of ion channel related diseases. Following an overview chapter summarizing the current state of.